Two-stage DEA method in identifying the exogenous factors of insurers’ risk and investment management efficiency - Yakob, Rubayah; Yusop, Zulkornain; Radam, Alias; Ismail, Noriszura (Penerbit Universiti Kebangsaan Malaysia, 2014)
The objective of this study was to identify the exogenous variables of risk and investment management efficiency by using a two-stage data envelopment analysis (DEA) method. The first stage involves obtaining the efficiency scores of risk and investment management via DEA that requires only the traditional inputs and outputs. In the second stage, the Tobit regression analysis is conducted in which the efficiency score obtained from the first stage is treated as a dependent variable, while the exogenous factors are considered to be independent variables. The exogenous factors consist of operating systems, organizational form, consumer preference and size. The results showed that the mutual company as well as the takaful system demonstrate better risk management performance than their stock and conventional system counterparts. In addition, size is also a significant indicator for risk management efficiency in which the larger insurer/takaful operator exhibits better risk management performance than the smaller one. However, consumer preference is found to be insignificantly correlated with the efficiency of risk management. In contrast, with risk management, organizational form, operating system and size are not indicators of the investment management efficiency, but consumer preference is significantly and positively associated with investment management efficiency.